Calculating the large leakage flux of a breached hydrocarbon trap using geophysical interpretation of a paleo-gas-water contact - Campbell, BL; Foschi, M; Cartwright, JA (Elsevier, 2022)
Integration of three-dimensional seismic and well data from the Northern Carnarvon Basin on the North West Shelf of Australia was used to assess the evidence for top seal breach of a paleo-gas accumulation. Several seismic indicators of vertical hydrocarbon leakage from the crest of the stratigraphic Mungaroo Trap point to a significant flux of gas within the past few hundred thousand years. Mapping of the top reservoir within the Triassic aged Mungaroo Formation revealed strong evidence for a paleo-gas-water contact (GWC), approximately 100 m down flank from the erosional crest of the trap. This contact conforms to structure and delimits an original volume of 1.1 trillion cubic feet (Tcf), based on reservoir property calibration from nearby wells. Mapping also revealed a present-day gas-water contact with a closed volume of 0.2 Tcf, 30 m down flank from the crest. This contact displays a discordant geometry indicative of a dynamic contact. The leakage zone is located directly above the crest of the structure. It is seismically well imaged and comprises seafloor pockmarks, shallow gas anomalies and gas hydrate anomalies. The presence of a leakage zone distributed vertically above a reservoir containing a present and paleo-GWC provides compelling evidence this trap has leaked by breaching of the top seal. Volumetric calculations using the two GWCs indicate that the Mungaroo Trap has been depleted by 0.9–1.1 Tcf. A dynamic-GWC indicates the leakage event within the trap has occurred recently. Analysis of dating of horizons correlated to the seafloor pockmarks places the leakage event at sometime within the last 300 Ka.